Copper deposition on metallic and non-metallic single particles via impact electrochemistry. (10th February 2022) - Oladeji, Abiola V.; Courtney, James M.; Rees, Neil V.
Highlights: Copper deposition via impact voltammetry onto au and ag nanoparticles. Deposition of copper demonstrated on 'non-metallic' fly-ash cenospheres. Direct spectrographic evidence provided for cu deposition on cenospheres. Demonstrated that impact voltammetry may become a sustainable recovery method. Abstract: This study demonstrates the possibility of depositing metals onto low-metal content particles via impact electrochemistry, a technique used to measure transient current signals (electrochemical impacts) produced from the collision between particles moving under Brownian motion and a potentiostated interface (Rees, 2014; Markham et al., 2020; Zhang and Zhou, 2020). The deposition of copper onto the surface of fly-ash cenospheres via electrochemical impacts is reported, along with its deposition onto silver and gold nanoparticles. A comparison with linear sweep voltammetry confirmed that impact signals correlated with deposition potentials (bulk and underpotential deposition). Reductive impact events were observed at potentials negative of −0.3 V (for Ag) and −0.1 V (for Au) (vs. MSE), with evidence for a change in coverage of deposition from ca. 103% at −0.1 V to 261% at −0.8 V vs. MSE for Au. Cenospheres were shown to be sufficiently electrochemically active to facilitate copper deposition, either on modified electrodes or showing transient impact spikes indicating copper deposition, which was confirmed via SEM/EDX and ICP-MS analysis. Graphical abstract: Image, graphical abstract